PENGARUH STRATEGI PEMASARAN DAN PELAYANAN PERGURUAN TINGGI TERHADAP KEPUASAN PELANGGAN PROGRAM UNGGULAN STRATA SATU (S1) SEKOLAH TINGGI ILMU ADMINISTRASI MANDALA INDONESIA (STIAMI) - Suparman Suparman (Institut Ilmu Sosial dan Manajemen STIAMI, 2016)
This study aims to determine the Effects of Marketing Strategies and Customer Satisfaction Quality Of Service / Student. Samples are 32 respondents drawn from a population of 36 students with Saturated sampling method. Data collection using questionnaire techniques, engineering research questionnaires, and observation. Processing of primary data using Analytical Methods Descriptive Analysis Method. From the discussion following results were obtained:First, There is the influence of Marketing (X1) on Customer Satisfaction / Student (Y) . Marketing significant value in the variable is equal to 0.966 (<0.05) which means that there is no influence of marketing variables partially on Customer Satisfaction. So H0 is rejected H1 is accepted. There is the influence of Quality of Service (X2) are positive and significant impact on Customer Satisfaction / Student (Y) . The value of significance in the variable quality of service is equal to 0.000 (< 0.01), which means with a confidence level of 99 percent variable partial Service Quality Customer Satisfaction is very real influence . So H0 H1 is rejected. There is positive and significant, Marketing Variables (X1) and Quality of Service (X2) jointly against Employee Morale (Y). Through the significance test using the F distribution, obtained Significance calculated F of 0.000 ( < 0.05 ) . This means that H0 is accepted or rejected H1. And the value of the coefficient of determination obtained with SPSS calculation amounted to 0.718. This indicates that 71.8 % of this value indicates that the total variation influences all independent variables to variable Quality Customer / Students. The influence of other variables beyond the variables studied was 28.2 percent. variables beyond the variables studied was 28.2 percent .Secondly, Strategy Marketing and Service Quality, both individually and jointly influence on customer satisfaction / student.